Human wastes? : contemporary forms of slavery and new abolitionism. - Casadei, Thomas (Soft Power, 2016)
After a general overview on the “slavery of the ancients” and the “slavery of the modern”, this paper focuses on the “slavery of the contemporaries” and its characteristics. The phenomenon can be described under a global perspective, bearing in mind the relevance of universal definitions such as those of “corps d’exception” and “human wastes” that can help to go towards a new abolitionism.